Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) inhibitors and the risk for neurocognitive adverse events: A systematic review, meta-analysis and meta-regression. (15th July 2021) - Hirsh Raccah, Bruria; Yanovsky, Alona; Treves, Nir; Rotshild, Victoria; Renoux, Christel; Danenberg, Haim; Eliaz, Ran; Matok, Ilan
Abstract: Background: It has been suggested that lipid lowering therapy causes impaired cognitive changes. The association between the use of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) inhibitors and the risk of neurocognitive adverse events remains unclear. This meta-analysis aims to assess neurocognitive safety of PCSK9 inhibitors in randomized controlled trials (RCTs). Methods and results: The research was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed (MEDLINE), Embase and Cochrane library were searched through September 2019. Selection criteria included RCTs that addressed to neurocognitive adverse events of participants using Alirocumab, Evolocumab or Bococizumab, with a follow up duration of at least 6 months. The search results were screened by two independent reviewers. Safety data from included papers were extracted. Random effects meta-analysis was used to pool results, and meta-regression was utilized when applicable. Twenty-one studies were included. Among 59, 733 patients, 31, 611 were treated with PCSK9 inhibitors. The follow-up period ranged from 24 weeks to 48 months. No significant difference in the incidence of neurocognitive adverse effects between the groups was identified (RR = 1.01, 95% CI: 0.86–1.19, I 2 = 3%). Similar results were seen in subgroup analysis for each of the medications (alirocumab- RR = 0.88, 95% CI: 0.72–1.08, I 2 = 0%, evolocumab- RR = 1.42, 95% CI: 0.74–2.73, I 2 = 55%). A meta-regression analysis for evolocumab revealed that prolonged study duration was associated with decreased risk for neurocognitive adverse events (βweek = −0.0037, p -value = 0.03). Conclusions: Pooled results of our meta-analysis and meta-regression show that exposure to PCSK9 inhibitors is not associated with an increased risk of neurocognitive adverse effects. Highlights: Lipid lowering therapy may be associated with impaired cognitive function. This meta-analysis included 21 studies with a total of 59, 733 patients. PCSK9 inhibitors are not associated with increased risk of neurocognitive adverse events. A longer exposure was associated with decreased RR for neurocognitive adverse events.